2009
DOI: 10.1089/pho.2008.2280
|View full text |Cite
|
Sign up to set email alerts
|

The Use of CO2 Laser in the Treatment of Peri-implantitis

Abstract: Different techniques have been used for the treatment of peri-implant defects. However, there are always questions about the issue of reosseointegration. The present paper explores the recent literature on the topic of peri-implantitis therapy, and presents a surgical protocol for implant surface decontamination using the CO(2) laser, grafting of the defect, and coverage with a membrane according to a clinical case. The results appear to be promising and may improve the long-term clinical outcomes of failing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 24 publications
(23 reference statements)
1
29
1
1
Order By: Relevance
“…The laser energy is absorbed in a very small volume of tissue, with precise removal of the irradiated tissue. It was demonstrated that Er:YAG-laser ablation comes with accurately limited lesion edges, low thermal damage, and corresponding undisturbed wound healing [40-42]. Due to these aspects the Er:YAG-laser was chosen for this study.…”
Section: Discussionmentioning
confidence: 99%
“…The laser energy is absorbed in a very small volume of tissue, with precise removal of the irradiated tissue. It was demonstrated that Er:YAG-laser ablation comes with accurately limited lesion edges, low thermal damage, and corresponding undisturbed wound healing [40-42]. Due to these aspects the Er:YAG-laser was chosen for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although peri-implantitis has been commonly treated with systemic administration of antibiotics, the success has been limited due to resistant strains of bacteria and ineffective antibiotic dosages61. Dental lasers have become popular for sterilization and cleaning of implant surfaces62.…”
Section: Implant Requirements and Desginmentioning
confidence: 99%
“…Dental lasers have become popular for sterilization and cleaning of implant surfaces62. It is believed that the decontamination of the implant is caused by the physical properties of the laser energy and its interaction with tissues, due to reflection, scattering, transmission, absorption and slight temperature elevation61,63. Other technique, laser peeing consists on surface bombardment with small spherical particles that causes small indentations or dimples using a laser beam striking a protective layer on the metallic surface64.…”
Section: Implant Requirements and Desginmentioning
confidence: 99%
“…Some studies 17,19,[117][118][119] have recommended the use of lasers as an adjunct to the conventional nonsurgical treatment of peri-implantitis. It has been shown that carbon dioxide (CO 2 ) and 980-nm diode lasers do not affect implant surfaces during irradiation of implant surfaces as compared with other lasers, such as Neodymium-doped Yttrium-Aluminum-Garnet (Nd:YAG) and Erbium:YAG laser.…”
Section: Lasers In the Treatment Of Peri-implant Diseasesmentioning
confidence: 99%